Improve Arabic language and Islamic skills with BISA system to Arab Village - Akzam, Ismail; Supriady, Harif; Alfitri, Alfitri (Linguistics and Culture Review, 2021)
Improving the ability of Arabic (bi-ah lughawiyyah 'arabiyyah) and Islam with the BISA system program. The purpose of this study is to describe the application of Arabic and Islamic learning in the Bogor Arabic Village explicitly. The research method uses qualitative. Data collection techniques: (a). Observation, (b). Interview (c). Documentation study. Conclusion (1). Arabic learning with the muhadatsah model for speaking skills and the qawa'id method for reading skills. (2). Islamic religious education starts from tahfizhul Quran, creed material, worship, morals, and muamalah. The learning process impact is mastering the Arabic language and applying it to the practice of Islam. It combines village and school concepts with the selection of beginner, intermediate, and advanced material.